The Russia account - Coonts, Stephen, 1946- (Regnery Fiction, 2019)
Burglar-turned-CIA-warrior Tommy Carmellini has starred in eight previous Coonts thrillers. With the help of his mentor, Admiral Grafton, Carmellini has always managed to foil his enemies. Discovering and defeating the powerful forces behind this massive bloodstained financial conspiracy that threatens the very foundations of the United States government, and maybe the life of the president of the United States, will be his most difficult challenge yet<U+2014>and perhaps, he suspects, an impossible one.